Evaluation of diagnostic accuracy of dual-energy computed tomography in patients with chronic thromboembolic pulmonary hypertension compared to V/Q-SPECT and pulmonary angiogram - Schüssler, Armin; Lug, Quirin; Kremer, Nils; Harth, Sebastian; Kriechbaum, Steffen D.; Richter, Manuel J.; Guth, Stefan; Wiedenroth, Christoph B.; Tello, Khodr; Steiner, Dagmar; Seeger, Werner; Krombach, Gabriele Anja; et al. (Frontiers in Medicine, 2023)
Purpose: The relevance of dual-energy computed tomography (DECT) for detection of chronic thromboembolic pulmonary hypertension (CTEPH) still lies behind V/Q-SPECT in current clinical guidelines. Therefore, the purpose of our study was to assess the diagnostic accuracy of DECT compared to V/Q-SPECT with invasive pulmonary angiogram (PA) serving as reference standard. Methods: 28 patients (mean age 62.1 years ± 10.6SD; 18 female) with clinically suspected CTEPH were retrospectively included. All patients received DECT with calculation of iodine maps, V/Q-SEPCT and PA. Results of DECT and V/Q-SPECT were compared and percent of agreement, concordance (utilizing Cohen’s kappa) and accuracy (kappa2) to PA were calculated. Moreover, radiation doses were analyzed and compared. Results: 18 patients were diagnosed with CTEPH (mean age 62.4 years ± 11.0SD; 10 female) and 10 patients had other diseases. Compared to PA, accuracy and concordance for DECT was superior to V/Q-SPECT in all patients (88.9% versus 81.3%; k=0.764 versus k=0.607) and in CTEPH patients (82.4% versus 70.1%; k=0.694 versus k=0.560). Furthermore, mean radiation dose was significantly lower for DECT versus V/Q-SPECT (p=0.0081). Conclusion: In our patient cohort DECT is at least equivalent to V/Q-SPECT in diagnosing CTEPH and has the added advantage of significantly lower radiation doses in combination with simultaneous assessment of lung and heart morphology. Hence, DECT should be the subject of ongoing research and should, if our results are further confirmed, implemented in future diagnostic PH algorithms at least on par with V/Q-SPECT.